2004
DOI: 10.1093/ajcn/79.6.1029
|View full text |Cite
|
Sign up to set email alerts
|

Low antioxidant vitamin intakes are associated with increases in adverse effects of chemotherapy in children with acute lymphoblastic leukemia

Abstract: A large percentage of children undergoing treatment for acute lymphoblastic leukemia have inadequate intakes of antioxidants and vitamin A. Lower intakes of antioxidants are associated with increases in the adverse side effects of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 25 publications
3
76
0
4
Order By: Relevance
“…Lower antioxidant intakes in a group of children with acute lymphocytic leukemia were associated with increases in adverse events during chemotherapy [77]. A decreased rate of chemotherapy-related nephro-and ototoxicity was only seen in the patients-supplemented with vitamins C, E, and selenium-who achieved the highest serum levels [78].…”
Section: Antioxidantsmentioning
confidence: 96%
“…Lower antioxidant intakes in a group of children with acute lymphocytic leukemia were associated with increases in adverse events during chemotherapy [77]. A decreased rate of chemotherapy-related nephro-and ototoxicity was only seen in the patients-supplemented with vitamins C, E, and selenium-who achieved the highest serum levels [78].…”
Section: Antioxidantsmentioning
confidence: 96%
“…Due to the limited data available to support the recommendation and level of dosing of antioxidants during cancer treatment, it leaves this topic in a state of controversy. Kennedy et al (11) advised that supplementation during treatment of antioxidants was not advocated due to the probable interference with cancer treatment, even though their study showed that the population group did not meet recommended dietary intake.…”
Section: Service (Nhs) As Such the Chairman Of The British Associatimentioning
confidence: 99%
“…Bleomycin, mitomycin-C). (11,19,27) Other drug classes such as taxanes, vinca alkaloids, anti-folates and nucleosides only generate low levels of free radicals. (28) In contrast radiation's main therapeutic effect occurs indirectly via the ionization of water molecules in the cytoplasm to ROS for example superoxide and hydroxyl radicals.…”
Section: Role Of Reactive Oxygen Species and Antioxidants In Cancer Tmentioning
confidence: 99%
See 2 more Smart Citations